“Culture-touristification” of colonial towns in the interior of Brazil - Karner, Marie Johanna; Husseini de Araújo, Shadia; Escher, Anton Jakob; Soares, Sávia Bona Vasconcelos; Ribeiro, Zenilda Lopes; Pöschl, Sebastian Nicolas; Ramos, Jade Oliveira; Rocha e Silva, Gabriel Rodrigues; Schneider, Katharina (ERDKUNDE, 2024)
The link between cultural heritage, touristification, and urban development has been extensively researched in larger cities with a strong appeal to international tourists. However, there is limited information on the relationship between these factors in smaller cultural heritage towns that rely only on regional or national tourism. This is also the case for small and medium-sized colonial towns in the Brazilian interior, which are the focus of this paper. We introduce the concept of “culture-touristification” as a form of touristification that is co-constituted by several interacting, culture-led sub-processes, such as patrimonialization, culturalization, festivalization, adventuring of landscapes, telenovelaization, and counter-culturalization. Based on this concept, we argue that culture-touristification drives the touristic transformation of small and medium-sized colonial towns in the interior of Brazil. However, the effects and the interplay of these sub-processes are different in these towns. Some of them may be more pronounced than others, and some may only be partially articulated, depending, for example, on their societal significance, the strategic orientation of responsible stakeholders, the resistance of local populations, or the geographical location of the towns. To illustrate this argument, we draw on case studies conducted in Cidade de Goiás and Pirenópolis, two small colonial towns in the state of Goiás, Brazil. Methods include in-depth and semi-structured interviews with residents and critical actors, mappings of building use in the town centers, participant observation, analysis of telenovelas and Instagram hashtags representing these cities, and document and data research.